2019
DOI: 10.1111/ics.12585
|View full text |Cite
|
Sign up to set email alerts
|

Expression and ultrastructural localization of plasmin(ogen) in the terminally differentiated layers of normal human epidermis

Abstract: ObjectivePlasmin, a relatively unspecific trypsin‐like serine protease, is involved in many physiological and pathological conditions, particularly in dermatoses with barrier impairment. It is secreted as the inactive zymogen plasminogen and is activated to plasmin by plasminogen activators, such as urokinase. There still exists a paucity of data on the precise localization of epidermal plasmin(ogen) within the epidermis and the stratum corneum. The aim of the present study was to get information about its ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…But where is epidermal plasmin synthesized and located ultra‐structurally? Based on immunogold labelling transmission electron microscopy, we explored this question together with Marek Haftek, CNRS, Lyon[40]. We did not find any plasmin labelling in the stratum spinosum and the lower parts of the epidermis in healthy skin.…”
Section: Maturation Pathways and Gradients In The Stratum Corneummentioning
confidence: 99%
“…But where is epidermal plasmin synthesized and located ultra‐structurally? Based on immunogold labelling transmission electron microscopy, we explored this question together with Marek Haftek, CNRS, Lyon[40]. We did not find any plasmin labelling in the stratum spinosum and the lower parts of the epidermis in healthy skin.…”
Section: Maturation Pathways and Gradients In The Stratum Corneummentioning
confidence: 99%
“…The transport of plasminogen to wounds is predominantly accomplished by its binding to plasminogen receptors present on inflammatory cells, mainly macrophages and granulocytes [ 17 , 18 ]. Moreover, it has been shown that plasminogen is synthesized also in normal human differentiated epidermal keratinocytes of the stratum granulosum, where it is largely associated with corneocyte envelopes and is not serum-born [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Facial SC is very different to other non-palmoplantar body sites; it is thinner and enriched in sebum but depleted of intercellular barrier lipids, such as ceramides, cholesterol and fatty acids. The facial SC also contains less NMF than other body sites and has higher proteolytic activities, including that of plasmin, a serine protease which is associated with the outer surface of corneocytes [5,6].…”
mentioning
confidence: 99%